Complete conditioning for golf - Draovitch, Pete 1961-; Simpson, Ralph (Human Kinetics, 2007)
"From the tee to the green, improve all aspects of your game with Complete Conditioning for Golf, a book/DVD package that presents the programs the pros use." "Golfers at all levels benefit from golf-specific training. This expert program begins with evaluation and moves through targeted strength, power, core, and flexibility exercises."